2020
DOI: 10.4236/as.2020.113016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Plant Growth Promoting Ability of <i>Bacillus amyloliquefaciens</i> Bc2 and <i>Trichoderma harzianum</i> TR <i>In Vivo</i>

Abstract: Bacillus amyloliquefaciens Bc2 and Trichderma harzianum TR were used to evaluate their growth-promoting activity on cultivated strawberries, under laboratory and field conditions, and we have noticed that the percentage of achene germination is important for ones treated with TR (=97%) followed by those treated with Bc2 strain (=90%) and the control (=84%). Inoculations on field showed that on untreated soil with insecticide, TR is effective and allows the development of plants and extends the duration of flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The work of Rababe et al [22] demonstrated the ability of T. harzianum on Fragaria vesca to stimulate germination via secreted phytohormones. It has also been shown that seed germination can be effective when seeds are pre-treated in a solution containing either T. harzianum or B. amyloliquefaciens, as the latter secrete phytohormones like gibberelin that break their dormancy [23].…”
Section: Effect Of the Formulation On Germinationmentioning
confidence: 99%
“…The work of Rababe et al [22] demonstrated the ability of T. harzianum on Fragaria vesca to stimulate germination via secreted phytohormones. It has also been shown that seed germination can be effective when seeds are pre-treated in a solution containing either T. harzianum or B. amyloliquefaciens, as the latter secrete phytohormones like gibberelin that break their dormancy [23].…”
Section: Effect Of the Formulation On Germinationmentioning
confidence: 99%